2000
DOI: 10.1094/pdis.2000.84.9.1046d
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence of Maize rayado fino virus in Maize in Argentina

Abstract: Symptoms of fine chlorotic stipple-striping of the veins, chlorosis, numerous dots and stripes, formation of holes in the leaf blade, and ears reduced in size, bearing few grains, were observed in maize crops in Tafí del Valle (Tucumán Province), Orán, El Galpón (Salta Province), Tilcara and Yaví (Jujuy Province), the subtropical area of northwest Argentina where the leafhopper vector Dalbulus maidis (DeLong & Wolcott) is present. Maize rayado fino virus (MRFV) was detected in these samples by a positive r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…This planthopper is a phloem feeder ( Brentassi, 2004 ; Brentassi and Remes Lenicov, 2007 ; Brentassi et al., 2019 ) and is the most important natural vector of Mal de Río Cuarto virus (MRCV) (Fijivirus, Reoviridae) ( Remes Lenicov et al., 1985 ). MRCV seriously affects maize ( Zea mays L.) production in northern and central provinces of Argentina ( Lenardón et al., 1998 ; Giménez Pecci et al., 2012 ) and also has been detected in Uruguay ( Ornaghi et al., 1999 ). Previous studies of D. kuscheli specimens demonstrated that the abdomen of nymphs and adults of both sexes and morphs (macropterous and brachypterous), as well as oocytes, contained YLS, indicating they are vertically transmitted ( Brentassi et al., 2014 ).…”
Section: Introductionmentioning
confidence: 99%
“…This planthopper is a phloem feeder ( Brentassi, 2004 ; Brentassi and Remes Lenicov, 2007 ; Brentassi et al., 2019 ) and is the most important natural vector of Mal de Río Cuarto virus (MRCV) (Fijivirus, Reoviridae) ( Remes Lenicov et al., 1985 ). MRCV seriously affects maize ( Zea mays L.) production in northern and central provinces of Argentina ( Lenardón et al., 1998 ; Giménez Pecci et al., 2012 ) and also has been detected in Uruguay ( Ornaghi et al., 1999 ). Previous studies of D. kuscheli specimens demonstrated that the abdomen of nymphs and adults of both sexes and morphs (macropterous and brachypterous), as well as oocytes, contained YLS, indicating they are vertically transmitted ( Brentassi et al., 2014 ).…”
Section: Introductionmentioning
confidence: 99%
“…The corn leafhopper Dalbulus maidis (De Long and Wolcott) (Hemiptera: Cicadellidae) is widely distributed in tropical areas of the Americas, from southern USA to temperate zones of Argentina ( Virla et al 1990/1991 ; Giménez Pecci et al 2002 ), and it is considered one of the most damaging species to corn due to its role as a vector of maize rayado fino virus, Spiroplasma kunkelii, and maize bushy stunt mycoplasm. These three pathogens, alone or in combination, are the ethiological agents of corn stunt, a disease that causes economic losses to corn crops in Mexico and Central and South America, and has been detected in restricted areas in the north of Argentina in 1990 ( Giménez Pecci et al 2000 ). Among the delphacid pests of maize is the planthopper, Delphacodes kuscheli Fennah (Hemiptera: Delphacidae) a native species of Argentina that has been reported as a vector of Mal de Río Cuarto virus ( Remes Lenicov et al 1985 ; Remes Lenicov and Virla 1999 ).…”
Section: Introductionmentioning
confidence: 99%
“…The loss of productivity caused by maize bushy stunt phytoplasma is expected and known from the scientific literature. 8,13 The other measures (grain per row, number of rows and weight of 100 grains) also reflected the losses caused by diseases transmitted by D. maidis. Our results showed that the potential damage caused by diseases transmitted by D. maidis was not negligible and should be considered even at low insect densities.…”
Section: Productivity Datamentioning
confidence: 99%
“…With the development of the disease, the points coalesce and form lines along the veins. 13 Early infections can lead to reduced growth and abortion of floral buds. 14 Despite the records of these diseases in tropical and temperate areas, the climatic variables that affect their incidence and severity remain poorly understood.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation